Clinical implication of triamcinolone in aqueous humor after depository sub‐Tenon application. Issue 11 (November 2017) - Xu, Xu; Han, Yin; Kong, Liping; Ding, Xiaoxu; Liu, Fang; Cheng, Lingyun
Abstract : Purpose : To determine the triamcinolone concentration in the aqueous humor after anterior sub‐Tenon injection versus posterior sub‐Tenon injection and the possible association between the levels of triamcinolone in the aqueous and the elevation in intraocular pressure (IOP). Setting : University teaching hospitals at Wenzhou and Shanghai, China. Design : Prospective case series. Methods : The aqueous humor was sampled and triamcinolone quantitated after anterior sub‐Tenon injection or posterior sub‐Tenon injection in a cohort of patients and in experimental rabbits. Patients' IOPs were measured before and up to 3 months after triamcinolone acetonide injection. Results : The study comprised 46 patients and 18 rabbits. The mean aqueous humor triamcinolone concentration in rabbit eyes and human eyes was significantly higher after an anterior sub‐Tenon injection than that after a posterior sub‐Tenon injection (rabbit eye: anterior sub‐Tenon injection, 2.67 ng/mL ± 0.78 [SD] and posterior sub‐Tenon injection 1.38 ± 0.48 ng/mL; human eye: 133.8 ± 149.2 ng/mL and 10.2 ± 10.9 ng/mL, respectively) (both P < .0001). After anterior sub‐Tenon injection, the mean triamcinolone concentration in the aqueous humor was significantly higher in human eyes than in rabbit eyes (133.8 ± 149.2 ng/mL versus 11.0 ± 8.1 ng/mL) ( P = .0003). The levels of triamcinolone in the human aqueous humor had a significant positive association with the elevation in IOP (β = 0.12, P = .026). Conclusions : The triamcinolone level in aqueous humor was associated with IOP elevation after sub‐Tenon application. Posterior sub‐Tenon injection with a small injection volume of concentrated suspension offered a better targeted delivery and might significantly reduce steroid‐associated IOP elevation.